(untitled) (Global Journal of Human-Social Science, 2013)
Mt Meru dominates the scenery and economy of the people living on its slopes. The lower slopes of the mountain provided fertile, well-watered land for the Meru and Arusha people for several centuries. Here they have developed "moral economies," innovative and well-managed mixed farming and agro-pastoral systems. The earliest Meru were Chaga speakers from western Kilimanjaro who expanded across the Sanya plains sometimes in the 17 th century. They were traditionally organised through "big men" known as vashili (singular nshili who supervised all important matters including traditional prayers, land conflicts, inheritance, farm boundaries, ceremonies and punishment. There were chiefs and elders who met under a large sacred tree, the mrin- garinga. Colonial occupation since the late 19 th century caused the closing of the land frontier on Meru and alienation of most of their land to white settlers. The Meru Land Case was a protest by Meru people, living in the Eastern part of what is now Arumeru District, against the allocation of their land to Europeans for development purposes. It is a tale of the Meru united to demand in an international forum the restitution of their rights to land. It is the story of Kirilo Japhet the first Tanzania to speak at the United Nations and in Kiswahili at that. Though they lost the case, it marked a milestone in i) African nationalist awakening and also opened the eyes of the British to forces at work against them